Study on Synthesis and Mechanism of Melt Polymerization of L-lactic Acid (Journal of Fiber Bioengineering and Informatics, 2018)
A two steps direct polymerization process was developed. The first step is to produceoligomer and then the oligomer of lactic acid is polymerized with binary catalyst tin chloride dihydrate/p-toluenesulfonic acid. In this way, the direct synthesis of poly (lactic acid)(PLLA) without anyorganic solvents was investigated. The properties and structures of products were characterized bynuclear magnetic resonance (NMR), FT-IR spectra, and so on. The results show that comparativelyhigh molecular weight polymer of lactic acid can be prepared by direct processing under appropriatetechnological conditions and that the melt polymerization of PLLA behaviors are as the second-orderreaction mechanism.
Keywords: melt polymerization; L-lactic acid; nuclear magnetic resonance (NMR); mechanism